Ligand exchange at tetra-coordinated beryllium centres - Buchner, Magnus R.; Cocic, Dusan; Ivlev, Sergei I.; Spang, Nils; Mueller, Matthias; Puchta, Ralph (Dalton Transactions, 2023)
Mono and dinuclear phosphine complexes of beryllium halides [(PMe3)2BeX2], [(PMe3)BeX2]2 and [(PCy3)BeX2]2 (X = Cl, Br, I) were synthesised and characterised via NMR and IR spectroscopy as well as single crystal X-ray diffraction experiments. Dissociation and ligand exchange processes at these complexes were investigated through variable temperature NMR experiments in combination with line shape analysis and complemented by quantum chemical calculations. The PMe3 dissociation energy is smallest in [(PMe3)2BeCl2], while PMe3 exchange is similar in energy in all mononuclear [(PMe3)2BeX2] complexes and follows an interchange mechanism. While [(PMe3)BeX2]2 dissociates homolytically, [(PCy3)BeX2]2 cleaves one phosphine ligand. These distinctive dissociation processes account for the different chemical behaviour of these complexes.
CRIS-Team Scopus Importer:2023-04-21